Problem-based learning on English for food and beverage operation subject course - Nyoman Kanca; Gede Ginaya; Ni Nyoman Sri Astuti (Politeknik Negeri Bali, 2020)
The 21st century learning paradigm is centered on some of the abilities that one of them is the ability for students to think critically, connect knowledge with the real world through problem-solving. Therefore, it is necessary to apply problem-based material by providing various problems. The learning process is directed so that students are able to solve problems systematically and logically. The purpose of this research is to investigate problem-based learning in the course of English for Food and Beverage Operation for students in semester 2 of Hotel Study Program, Tourism Department, Bali State Polytechnic in 2018/2019 academic year. This classroom action research is a descriptive qualitative in which data is collected through three learning cycles with planning, action, observation, and reflection. The results showed that the problem-based learning model for the second semester students in the English for Food and Beverage Operation course can improve students' speaking ability. The improvement is also supported by increased learning motivation and interest.